The applications and mechanisms of Rosmarinus officinalis L. in the management of different wounds and UV-irradiated skin - Xu, Jianwen; Li, Ting; Li, Fei; Qiang, Hong; Wei, Xiaoxiao; Zhan, Ruiwen; Chen, Yun (Frontiers in Pharmacology, 2025)
Chronic wounds, especially non-healing wounds, significantly affect patients’ quality of life and raise the costs of therapy. Wound healing is a complicated process involving interdependent stages, which may be impaired and delayed by infections with multi-drug resistant pathogens. Current medical strategies for wound healing, especially the treatment of non-healing wounds, exert limited therapeutic effects, thus become a dramatic challenge for modern medicine. There has been growing interest in exploring complementary approaches to enhance the wound healing process, and complementary therapy using herbs and their related products has gained increasing attention. Apart from skin wounds, dermal pathological changes caused by UV irradiation, may also benefit from such complementary therapy. The antimicrobial, anti-inflammatory, antioxidant, analgesic and collagen-promoting properties of extract from Rosmarinus officinalis L. (rosemary) have all been considered to contribute to the beneficial effects on different stages and multiple aspects of skin recovery after various wounds or UV irradiation. This review aims to summarize the applications and their underlying mechanisms of rosemary as part of the complementary therapy for injured and UV-irradiated skin based on the currently available evidence. The medicinal properties of rosemary and its application in wound dressing are first discussed, followed by summarization of its application in different types of wounds. A conclusion is reached and future directions are discussed. As research in this area continue to evolve, rosemary-derived products may become an integral part of holistic wound care strategies, offering a complementary approach to conventional treatments.